Siehe – der Mensch (Joh 19,5) - Wischmeyer, Oda (Kerygma und Dogma. Zeitschrift für theologische Forschung und kirchliche Lehre, 2024)
This article puts the current debate on the anthropology of the New Testament in the larger context scientific anthropology. Four basic features of New Testament discourse on the human being are outlined. In the following, the narrative portrayal of human beings and the portrayal of Jesus as a human being in the Synoptic Gospels are analyzed and related to each other.
CRIS-Team Scopus Importer:2024-11-01